Strategi Komunikasi Direktorat PemberdRawan ayaan Alternatif BNN dalam Membina Masyarakat Daerah Narkoba Kampung Pertanian Klender - Anggle Elizabeth; Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The impact of the spread and illicit drug trafficking which is increasingly widespread in Indonesia needs to be done in every environment that is affected by drugs. This recovery process must use an institution whose background is to eradicate drugs and be able to establish good communication with fostered residents in each drug-affected environment. This study explains the role of the Directorate of Alternative Empowerment of the National Narcotics Agency in carrying out recovery in drug-affected environments. The purpose of this study is to describe the ability of an institution in fostering citizens in reaching the recovery stage as well as obstacles that occur when the environmental recovery of the drug takes place. This research methodology uses a qualitative approach to the type of descriptive research and uses purposive sampling as an informant selection technique. The results of this study indicate that communication strategies that will be more effective to improve the image of the National Narcotics Board in drug-affected environments.